Evaluating an innovative integrated training for child and youth services: Lessons learned. (June 2022) - Coll, Kenneth M.; Stewart, Roger A.; Day, Alexander; Scholl, Stacey; Hauser, Nicole
Abstract: This article highlights one child and youth services agency's journey to develop and pilot a system for tracking training effectiveness for staff. Given the importance of intentional and strong staff training to the success of an agency, the purpose of this study was to report training outcomes across four-time intervals (i.e., immediately after training considered here as baseline, 6 months, 12 months, and 18 months) using a tracking system based on best practices in staff development. Results indicated that the tracking system allowed this agency to measure and describe post-training outcomes for staff across the four-time intervals. It can be inferred that such training positively influenced youth outcomes. Specifically, the training and follow-up expanded staff's ability to effectively internalize concepts and be more intentional with their time for the benefit of youth care.